KELAYAKAN BUKU POP UP PEKALONGAN THE WORLD’S CITY OF BATIK: WARNA-WARNI BATIK PEKALONGAN SEBAGAI MEDIA EDUMOTIK (EDUKASI DAN PROMOSI BATIK) - Aulia, Hanindya Restu; Pramitasari, Afrinar; Widadi, Zahir (BAPPEDA Kota Pekalongan, 2015)
THE PROBLEM OF THIS RESEARCH WAS HOW FEASIBILITY OF THE PEKALONGAN THE WORLD'S CITY OF BATIK: COLORFUL BATIK PEKALONGAN POP UP BOOKS AS MEDIA EDUCATION AND THE PROMOTION OF PEKALONGAN BATIK (EDUMOTIK). THE PURPOSE OF THIS STUDY TO DETERMINE THE FEASIBILITY OF A POP UP BOOK PEKALONGAN THE WORLD'S CITY OF BATIK: COLORFUL BATIK PEKALONGAN AS MEDIA EDUCATION AND THE PROMOTION OF PEKALONGAN BATIK (EDUMOTIK). THIS RESEARCH USES DESCRIPTIVE METHOD. BASED ON FEASIBILITY ANALYSIS OF POP-UP BOOKS PEKALONGAN THE WORLD'S CITY OF BATIK: COLORFUL BATIK PEKALONGAN AS MEDIA EDUCATION AND THE PROMOTION OF PEKALONGAN BATIK (EDUMOTIK) CAN BE DRAWN THE CONCLUSION THAT (1) THE MATERIAL PRESENTED IN ACCORDANCE WITH THE THEORY OF PEKALONGAN BATIK; (2) THE LANGUAGE USED IS APPROPRIATE TO THE AGE OF THE TARGET; (3) POP UP WHICH PRESENTED INTERESTING AND APPROPRIATE TO THE STORY; (4) ABLE TO ATTRACT READERS. OVERALL THE BOOK POP UP PEKALONGAN THE WORLD'S CITY OF BATIK: COLORFUL BATIK PEKALONGAN HAS BEEN QUALIFIED AS A MEDIUM OF EDUCATION AND PROMOTION OF PEKALONGAN BATIK (EDUMOTIK).